Tunable high-temperature itinerant antiferromagnetism in a van der Waals magnet - Junho Seo; Eun Su An; Taesu Park; Soo-Yoon Hwang; Gi-Yeop Kim; Kyung Song; Woo-suk Noh; J. Y. Kim; Gyu Seung Choi; Minhyuk Choi; Eunseok Oh; Kenji Watanabe; et al. (Nature Communications, 2021)
Metallic van der Waals magnets have considerable technological promise, due to their ability to be strongly coupled with electronic currents and integrated in two dimensional heterostructures. Here, Seo et al. demonstrate highly tunable itinerant antiferromagnetism in a van der Waals magnet.